A case of flexor tenosynovitis caused by Cyberlindnera rhodanensis – First reported human infection - Sarah Kim; Stephanie Spivack (Medical Mycology Case Reports)
We report a case of an immunocompetent individual who was diagnosed with fungal tenosynovitis of the wrist caused by Cyberlindnera rhodanensis, a yeast in the Saccharomycetales order that has never been reported to cause infections in humans. The yeast grew in routine culture and was sent to a reference laboratory for identification and susceptibility testing. The patient ultimately received six surgeries and five months of antifungal therapy, including micafungin and voriconazole, before clinical resolution.